2021
DOI: 10.3390/d13040172
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence and Polyphyly in the Octocoral Genus Swiftia [Cnidaria: Octocorallia], Including a Species Impacted by the DWH Oil Spill

Abstract: Mesophotic coral ecosystems (MCEs) are recognized around the world as diverse and ecologically important habitats. In the northern Gulf of Mexico (GoMx), MCEs are rocky reefs with abundant black corals and octocorals, including the species Swiftia exserta. Surveys following the Deepwater Horizon (DWH) oil spill in 2010 revealed significant injury to these and other species, the restoration of which requires an in-depth understanding of the biology, ecology, and genetic diversity of each species. To support a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Such discordance has been attributed to Introgression, hybridization, and incomplete lineage sorting (e.g., Toews and Brelsford, 2012) and is not uncommon. For example, among octocorals, Frometa et al (2021) found that nuclear 28S rRNA and mitochondrial MutS sequences were not phylogenetically congruent in work with the genus Swiftia. As the mitochondrial protein coding genes are effectively a single locus, high concordance among mitochondrial genes can lead to high bootstrap values even when the tree topology reflects the evolutionary history of the mitochondrion rather than the organism.…”
Section: Mitochondrial and Nuclear Phylogenies Of Pennatulaceamentioning
confidence: 99%
“…Such discordance has been attributed to Introgression, hybridization, and incomplete lineage sorting (e.g., Toews and Brelsford, 2012) and is not uncommon. For example, among octocorals, Frometa et al (2021) found that nuclear 28S rRNA and mitochondrial MutS sequences were not phylogenetically congruent in work with the genus Swiftia. As the mitochondrial protein coding genes are effectively a single locus, high concordance among mitochondrial genes can lead to high bootstrap values even when the tree topology reflects the evolutionary history of the mitochondrion rather than the organism.…”
Section: Mitochondrial and Nuclear Phylogenies Of Pennatulaceamentioning
confidence: 99%